Managing Spider Mites in Florida Hops - Hugh A. Smith; Shinsuke Agehara (EDIS, 2023)
This publication is designed to provide information on managing spider mites on hops grown in Florida to hops growers, UF/IFAS Extension agents, and other crop protection professionals. Hops (Humulus lupulus L.) (Cannabinaceae), a new crop for Florida, has been studied at the UF/IFAS Gulf Coast Research and Education Center (GCREC) since 2016. A fall and spring crop have been cultivated each year, providing opportunity to observe pests and evaluate pest management strategies over several seasons. Spider mites (Trombidiformes: Tetranychidae) have been a consistent pest of hops at GCREC each season. Information on chemical and biological control is provided.